Game-Based Development Using the Hannafin and Peck Model for the Tajwid’s Learning Media - Nazliati; Rita Sari; Alfiatunnur (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
The pedagogical imperative to enhance Tajweed proficiency, a fundamental Islamic educational tenet, necessitates innovative teaching methodologies, especially for learners at the concrete operational stage. This study introduces